2022
DOI: 10.1111/cod.14130
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy in children with and without atopic dermatitis: An Italian multicentre study

Abstract: Background Contact allergy and atopic dermatitis (AD) are both common inflammatory T cell‐mediated diseases and many factors may influence the prevalence of contact allergy in AD patients. In children, their possible correlation was debated with conflicting results. Objectives The present study aimed to assess the prevalence of contact sensitivity in children and to investigate the association with AD. Materials and methods A retrospective multicentre study on children aged from 0 to 14 years patch tested betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(61 citation statements)
references
References 49 publications
1
58
2
Order By: Relevance
“…We found that cobalt reactions in children were not associated with sex, atopic history, race or employment. This is in contrast to other studies which found that children with cobalt allergy are more likely to be female 4 and have a history of atopic dermatitis 16 or atopy. 8 A Polish study of 9320 children found that every second child with atopic eczema has a positive patch test result, and every third child ultimately was diagnosed with ACD.…”
Section: Sourcescontrasting
confidence: 99%
“…We found that cobalt reactions in children were not associated with sex, atopic history, race or employment. This is in contrast to other studies which found that children with cobalt allergy are more likely to be female 4 and have a history of atopic dermatitis 16 or atopy. 8 A Polish study of 9320 children found that every second child with atopic eczema has a positive patch test result, and every third child ultimately was diagnosed with ACD.…”
Section: Sourcescontrasting
confidence: 99%
“…39,41 Patients with AD who develop EH tend to have more severe AD, earlier-onset AD, high total serum immunoglobulin E/peripheral eosinophils, and presence of other atopic diseases such as food allergies and asthma, as compared to their AD counterparts without EH. 39,41 It may be confused with impetigo, especially in patients with a history of severe AD (EH incognito) or in the early stages with AD itself. 39,41 Bacterial positivity on skin culture does not exclude EH.…”
Section: Eczema Herpeticummentioning
confidence: 99%
“…Impetigo is a superficial bacterial infection caused mainly by Staphylococci and Streptococci, and takes the form of pain, erythema, and serum scabs 39 . It may therefore be confused with AD or coexist with it 39 .…”
Section: Differential Diagnosismentioning
confidence: 99%
See 2 more Smart Citations